AN ANALYSIS DEIXIS IN “NOM NOM’S ENTOURAGE” MANUSCRIPT ON WE ARE BARE BEARS MOVIE SEASON - Wasdili, Arni Rahmah; Santoso, Iman (IKIP Siliwangi, 2021)
The tittle of this research is An AnalysisDeixis in “Nom nom’s Entourage” Manuscript on We are Bare BearsMovie Seaso. Deixis is one of branch from pragmatics that shown relation between language and context in that language it self. The aim from this research is to know and identify the type of deixis in Nom nom’s Entourage movie season. That have some steps to collecting the data firs is watching the We Are Bare Bears movie season with Nom nom’s Entourage title. Second is reading the script of that movie. Third, selecting and collect the data. Fourth is classifying the type of deixis and the last is produce the conclution. This research using descriptive qualitative method to analyze the data. The result from this research is that have five type of deixis there are person deixis, time deixis, place deixis, social deixis and discourse deixis. Person deixis divided to three part there are firs person as speaker, second person as hearer and third person as other, with 195 word in that movie. Time deixis shows a certain period of time, consist of 10 word in that movie. Place deixis describe the location in a conversation, consist of 26 word in that movie. Social deixis is show how the social differences when talking with other, consist of 18 word in that movie. Discourse deixis is show deitic expressions which point to prior succeeding parts of the discourse with 4 word in that movie. Keywords: Pragmatics, Deixis, Movie